Investigation of the relationship between contrast nephropathy development and body mass index in patients receiving contrast media in the emergency department - Dilek, Mehmet Seyit Şerif; İşler, Yeşim and Kaya, Halil and Yüksel, Melih (The European Research Journal, 2022)
Objectives: This study aims to investigate the risk factors in patients presenting to the emergency department, undergoing contrast-enhanced computed tomography (CT), and developing contrast-induced nephropathy (CIN) and whether there is a relationship between CIN and body mass index (BMI). Methods: A total of 336 patients presenting to the emergency department between 15.3.2019 -31.12.2019 and underwent CT by administering intravenous (IV) contrast agent (CA) were prospectively analyzed. Patients’ age, gender, chronic diseases, height, weight, BMI, and hospitalization or discharge information were recorded. Control creatinine was measured at 72nd and 120th hours. Patients who developed CIN were recorded. Results: The mean age of the patients was 57 years (min: 18-max: 96) and 56.5% were male. CIN developed in 6.5% of the patients. Congestive heart failure (CHF) was associated with the increased risk of CIN (p = 0.045). There was a significant increase in CIN risk in patients aged 40-70 years (p = 0.008). The risk of CIN development was increased with advanced age (p = 0.002). Dialysis was required in 13% of patients who developed CIN. There was no significant relationship between BMI and CIN development (p = 0.740). Conclusions: We did not find a significant relationship between BMI and CIN. However, the risk of CIN development was higher in patients over 40 and especially in patients with CHF.